2018
DOI: 10.1080/00224499.2018.1544604
|View full text |Cite
|
Sign up to set email alerts
|

Social Ecological Factors of Sexual Subjectivity and Contraceptive Use and Access Among Young Women in the Northwest Territories, Canada

Abstract: Adolescent women in the Northwest Territories (NWT), Canada, experience many sexual health challenges that are linked to a history of colonization and intergenerational effects of trauma. This study was informed by social ecological theory and explored how young women in the NWT develop sexual subjectivity within the context of contraception use and access during this time of decolonization. A total of 41 participants (aged 13 to 17 years) attended the Fostering Open eXpression among Youth (FOXY) body-mapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…These results show that the primary source of information about sexuality for adolescent girls is the women of their family, in addition to teachers and friends. Therefore, it is reported that adolescents could increase their veridic-scientific knowledge through comprehensive sexual health education in school, which is focused on developing self-esteem and self-efficacy [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…These results show that the primary source of information about sexuality for adolescent girls is the women of their family, in addition to teachers and friends. Therefore, it is reported that adolescents could increase their veridic-scientific knowledge through comprehensive sexual health education in school, which is focused on developing self-esteem and self-efficacy [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that physicians were unsatisfied with their current knowledge of EC and felt uncomfortable due to inexperience with its use. They also felt it an inappropriate topic to be discussed at routine consultations due to religious/ethical/cultural reasons as it could promote promiscuity [22,38]. Unwillingness at the provider level can have significant implications as couples might not be able to obtain timely information to initiate contraception.…”
Section: Plos Onementioning
confidence: 99%
“…EST hypothesizes that an individual's development and behavior is defined through an interrelationship between the individual and different environments that can influence an individual response at different levels. This framework emphasizes that individual behaviors and perceptions are influenced by intra and interpersonal attributes and wider societal-community contexts [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The Fostering Open eXpression among Youth (FOXY) body-mapping intervention exemplified an approach to promoting healing from the colonial legacy. This intervention recreated spaces of mutual learning and ritual to help youth make informed and autonomous decisions about their sexual health (Lys et al, 2019).…”
Section: Addressing the Effects Of Colonizationmentioning
confidence: 99%